2023
DOI: 10.3390/math11224708
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm That Adjusts the Stepsize to Be Self-Adaptive with an Inertial Term Aimed for Solving Split Variational Inclusion and Common Fixed Point Problems

Matlhatsi Dorah Ngwepe,
Lateef Olakunle Jolaoso,
Maggie Aphane
et al.

Abstract: In this research paper, we present a new inertial method with a self-adaptive technique for solving the split variational inclusion and fixed point problems in real Hilbert spaces. The algorithm is designed to choose the optimal choice of the inertial term at every iteration, and the stepsize is defined self-adaptively without a prior estimate of the Lipschitz constant. A convergence theorem is demonstrated to be strong even under lenient conditions and to showcase the suggested method’s efficiency and precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In the above-mentioned work and related literature, we found that the step size, which is under the control of norm ∥A * A∥, is required for the convergence of iterative schemes. To overcome this regulation, a new form of iterative schemes have been proposed, see, e.g., [16][17][18][19]. L ópez et al [20] proposed a relaxed iterative scheme for (S p FP):…”
Section: Introductionmentioning
confidence: 99%
“…In the above-mentioned work and related literature, we found that the step size, which is under the control of norm ∥A * A∥, is required for the convergence of iterative schemes. To overcome this regulation, a new form of iterative schemes have been proposed, see, e.g., [16][17][18][19]. L ópez et al [20] proposed a relaxed iterative scheme for (S p FP):…”
Section: Introductionmentioning
confidence: 99%